The Antecedents, Consequences, and Mediating Role of Organizational Ambidexterity - Gibson, Cristina B.; Birkinshaw, Julian (Academy of Management Journal, 2004)
We investigated contextual organizational ambidexterity, defined as the capacity to simultaneously achieve alignment and adaptability at a business-unit level. Building on the leadership and organization context literatures, we argue that a context characterized by a combination of stretch, discipline, support, and trust facilitates contextual ambidexterity. Further, ambidexterity mediates the relationship between these contextual features and performance. Data collected from 4,195 individuals in 41 business units supported our hypotheses.